Influence of Location, School Quality, and Promotion on Students' Decisions in Continuing Levels at SMK Mataram Semarang - Riyono, Riyono; Ristanto, Hesti; Susilo, Bambang Widjanarko (BIMA Journal (Business, Management, & Accounting Journal), 2023)
This study aims to determine the effect of location, school quality, and promotion on student decisions. The population in this study were all 10th grade students of SMK Mataram Semarang from 4 majors, namely culinary, fashion, hospitality, and automotive. Of the 220 students, the researchers required 146 students as a sample using the solvency formula.The results of this study can be concluded that: Location has no significant positive effect on student decisions, school quality has a significant positive effect on student decisions, and Promotion has a significant positive effect on student decisions.